Fostering effective vocabulary retention among primary school students: a case study - Sahin, Damla; Yavuz, Mehmet Ali (Frontiers in Psychology, 2025)
IntroductionNumerous studies on vocabulary acquisition have prioritized form-first instruction, focusing on spelling and pronunciation before meaning. However, cognitive theories suggest that introducing meaning first may enhance vocabulary retention by engaging deeper semantic and conceptual processing.MethodsThis quasi-experimental study explored the effects of meaning-first versus form-first vocabulary instruction on bilingual primary school students in Cyprus. Over a 12-week period, 57 fourth-grade students were divided into two groups: one receiving meaning-first instruction and the other form-first instruction. The Self-Report Vocabulary Mastery Scale (SRVMS) was used to assess both word knowledge and contextual application.ResultsFindings revealed that while both groups improved, the meaning-first group significantly outperformed the form-first group in vocabulary acquisition and sentence-level usage. Statistical analysis showed a large effect size (Cohen's d = 1.37), indicating a strong advantage for meaning-first instruction in fostering lexical encoding and retrieval.DiscussionThe results align with theories of cognitive load, depth of processing, and working memory, offering practical implications for inclusive and sustainable language education.